Particle–Continuum Coupling and its Scaling Regimes: Theory and Applications. Issue 5 (19th March 2020) - Delle Site, Luigi; Praprotnik, Matej; Bell, John B.; Klein, Rupert
Abstract: This work is motivated by the goal of designing simulation software for technical devices that, at their functional core, rely on atomistic‐scale processes embedded in a larger‐scale fluid environment. The core of the problem is the conceptual and technical approach for coupling particle and continuum representations of a fluid. The state of the art for key aspects including physical modeling, mathematical formalization, computational implementation, and applications, is discussed and organized in a consistent picture across the relevant physical regimes. Abstract : A current challenge facing particle‐based simulation of condensed matter systems is to build an efficient and well‐justified framework that consistently links regions in space with atomistic, coarse‐grained, and continuum representations of the pertinent processes through coupling conditions that properly reflect the scale‐dependent physics at the respective interfaces. The current theoretical state of the art of the field is reported from an interdisciplinary point of view intended to support the establishment of a common platform for colleagues from different scientific communities.